PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN DAN PAYMENT GATEWAY BERBASIS QRIS TERHADAP KINERJA UMKM DI KECAMATAN BUSUNGBIU - Komang Elsa Nindy Andriani; I Gst Ayu Ketut Rencana Sari Dewi; I Made Dwita Atmaja (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of Financial Literacy, financial inclusion and QRIS-based payment gateway on the performance of UMKM in Busungbiu District. This study is an associative or causal relationship study using a quantitative approach. The population in this study were UMKM in Busungbiu District, which were 3,359 UMKM. The sampling method used was purposive sampling and 89 UMKM were obtained that already had business licenses. The data analysis technique used was multiple linear regression analysis using the SPSS version 30 program in the trade sector. The results of the study showed that financial literacy, financial inclusion, and QRIS-based payment gateways partially had a positive and significant effect on UMKM performance.